Physically entrapped gelatin in polyethylene glycol scaffolds for three-dimensional chondrocyte culture. (September 2016) - Zhang, Jingjing; Mujeeb, Ayeesha; Feng, Junxia; Li, Yijiang; Du, Yanan; Lin, Jianhao; Ge, Zigang
Developing tissue-engineered constructs for clinical use must satisfy the fundamental biologic parameters of biocompatibility, cell adhesiveness, and biodegradability. Physical entrapment of bioactive agents into synthetic polymers, as three-dimensional scaffolds, holds great promise for cell culture applications. Here, in an attempt to elucidate the effects of physical interlocking of natural and synthetic gel networks on cell responses within three-dimensional microenvironments, gelatin (of different concentrations) was physically incorporated into macroporous polyethylene glycol (PEG) hydrogels to fabricate PEG-GEL1 (10:1, PEG:gelatin) and PEG-GEL5 (10:5, PEG:gelatin). The effect of the physically entrapped gelatin on primary chondrocytes was investigated in relation to cell distribution, morphology and viability, proliferation, gene expression, and extracellular matrix accumulation in vitro. Our findings have shown successful incorporation of two different concentrations of gelatin into polyethylene glycol macroporous hydrogels through physical mixing. These physical blends not only enhanced chondrocyte adhesion and proliferation but also boosted gene expression of collagen II and aggrecan after 14 days in culture. Although results demonstrated that gelatin levels dropped sharply in PEG-GEL1 and PEG-GEL5 in the first 7 days, however evidently, after days 14 and 21 gelatin levels in both groups remained substantially unchanged and in turn enhanced glycosaminoglycan formation in vitro. Thus, the modification of polyethylene-glycol-based scaffolds with physically entrapped gelatin may be sufficient for dictating three-dimensional microenvironments for chondrocyte cultures.